2022
DOI: 10.3390/ijerph19084519
|View full text |Cite
|
Sign up to set email alerts
|

An Inclusive Leadership Framework to Foster Employee Creativity in the Healthcare Sector: The Role of Psychological Safety and Polychronicity

Abstract: Creativity at the level of employees is of utmost importance for every sector of an economy, with no exception to a healthcare system. The reason why employee creativity is important lies in the fact that employees have profound knowledge of their job and thus can serve as a source of meaningful innovation in an organization. Research shows that employee creativity is largely dependent on leadership. Corporate leaders significantly influence subordinates’ behavior. However, with the economic development, globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 47 publications
(43 reference statements)
3
51
0
3
Order By: Relevance
“…The variables in this study (ESL, EPEB, GSE, and GPOS) were measured by adapting items from different sources. Given that their reliability and validity are known, we followed other authors in using pre-existing scales [26,78].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables in this study (ESL, EPEB, GSE, and GPOS) were measured by adapting items from different sources. Given that their reliability and validity are known, we followed other authors in using pre-existing scales [26,78].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the role of personal factors such as values [20,21], personality [22], emotions [23], and motivation [24] was also highlighted in the previous literature. Recently, organizational interest in understanding the role of corporate leaders in influencing employee behavior has increased [25,26]. In particular, the role of an environmentally specific servant leadership style (ESL) to spur the PEB of employees was realized at different levels [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that leader humor is thought to be an effective tool for cultivating a creative environment ( Amjed and Tirmzi, 2016 ; Peng et al, 2020 ; Yang et al, 2021 ; Fu et al, 2022 ), the influence of leader humor on employee creativity is rarely investigated. The few scholars who have studied the relationship between leader humor and employee creativity put leaders and employees at the same level of research, i.e., individual level, and the theoretical perspective of the research is limited to the relatively single perspective, i.e., social exchange theory.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership literature suggests that corporate leaders are in great positions to influence employees’ attitudes and behaviors [ 5 , 41 , 42 ]. While different leadership styles have been discussed previously to influence different employees’ outcomes, recently, the concept of ethical leadership has gained momentum.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Considering different negativities associated with turnover, contemporary enterprises from every sector of an economy place a great emphasis on retaining their employees and understanding the factors contributing to turnover. When linked to the healthcare system, an increasing turnover rate has more consequences than other sector because the healthcare sector worldwide is identified as a sector facing resource scarcity [ 4 , 5 ]. Studies have shown that turnover has been increasing in healthcare systems globally [ 6 ].…”
Section: Introductionmentioning
confidence: 99%